Experience in use of small valve prostheses in adults with narrow valve ring of the aortic valve - O. A. Shapovalova; M. S. Bula; O. U. Pukas; S. V. Varbanets; O. D. Bablyak (Ukrainian Journal of Cardiovascular Surgery, 2016)
We selected 28 consecutive cases, in which valve prosthesis sized 18–20 mm were used, from 339 patients, who underwent aortic valve replacement. The prosthesis selection was based on the effective orifice area index (iEOA). 18 patients had no patient-prosthesis mismatch (iEOA ≥ 0,85 sm2/m2), ten – had moderate patient-prosthesis mismatch (iEOA 0,84–0,65 sm2/m2) and no patient had severe patient-prosthesis mismatch (iEOA ≤ 0,65 sm2/m2).Highest values of maximal valve gradients were measured in younger patients. Most patients (n=19) noted good quality of life, no edemaes, no shortness of breath and tolerated physical exertion well.Small aortic valve prostheses using in aged patients is acceptable, even if moderate patient-prosthesis mismatch exists.